(untitled) (American Journal of Islam and Society, 1994)
The purpose of this paper is to examine the curtent debates within the American Muslim community regatding the expression of Muslim religious commitment in American life. The size of the community is now estimated to exceed four million (Stone 1991), and the numlxx of Muslim immigrants entering the United Stab has more than doubled since 1960. During the same period, the number of American converts to Islam has also risen. Both the growth of the Muslim community in mxent yeas, in the United Stab and worldwide, and the increasing number of Muslims in "diaspora" as Muslim labor migration continues, which has resulted in a heightened sense of "minority" status among Muslims (Haddad 1991), have raised many crucial questions concerning religious expression: Should Muslims remain marginal to secular power relations in accordance with the teachings of classical Islam or adopt a strategy of assimilation which, in the American context, includes the p d t of claims to equal protection under civil law? What happens to a religious community, such as the Muslim community, as it develops the institutional organization it needs to preserve its identity in a non-Islamic society? Can it still remain open to the sowe of inspiration and spiritual guidance located in the fold of the Islamic world? Or does the locus of authority shift? Changing circumstances require adaptation, and yet that adaptation involves the risk of losing the connection to the heatt of the original insight and cultm. Conflicting tesponses to these and related questions raise issues of self-representation and lifwle. The resulting theological and ideological debates within the Muslim community itself provide and refine various models for Muslim minority life in a non-Islamic envimnment. They also illustrate the tension between alienation and integration ...